2000
DOI: 10.1093/jn/130.5.1189
|View full text |Cite
|
Sign up to set email alerts
|

Carotenoid Bioavailability in Humans from Tomatoes Processed in Different Ways Determined from the Carotenoid Response in the Triglyceride-Rich Lipoprotein Fraction of Plasma after a Single Consumption and in Plasma after Four Days of Consumption

Abstract: Tomatoes are the main dietary source of lycopene, and the bioavailability of lycopene from tomato paste is higher than that from fresh tomatoes. We investigated systematically the effect of mechanical homogenization and heating on the bioavailability of carotenoids from canned tomatoes. Further, we compared the carotenoid response in triglyceride-rich lipoproteins (TRL) after single consumption with the change in fasting plasma carotenoid concentrations after 4 d of daily consumption. In a split plot design, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(24 citation statements)
references
References 20 publications
0
22
1
1
Order By: Relevance
“…The results of the current study seem to be in contrast with the results of the in vivo study of van het Hof, de Boer, et al (2000). These authors observed that HPH at 200 bar enhanced the lycopene response in the triglyceride-rich lipoprotein fraction of plasma.…”
Section: Influence Of Hph On In Vitro Bioaccessibility Of Lycopenecontrasting
confidence: 99%
See 2 more Smart Citations
“…The results of the current study seem to be in contrast with the results of the in vivo study of van het Hof, de Boer, et al (2000). These authors observed that HPH at 200 bar enhanced the lycopene response in the triglyceride-rich lipoprotein fraction of plasma.…”
Section: Influence Of Hph On In Vitro Bioaccessibility Of Lycopenecontrasting
confidence: 99%
“…These authors observed that HPH at 200 bar enhanced the lycopene response in the triglyceride-rich lipoprotein fraction of plasma. The discrepancy in the results might be caused by the fact that van het Hof, de Boer, et al (2000), van het used canned tomatoes that had received a 55 min heat treatment at 100°C before the HPH. Furthermore, in the study of van het Hof, de Boer, et al (2000) the tomato products were served to volunteers together with pasta, ham and sauce.…”
Section: Influence Of Hph On In Vitro Bioaccessibility Of Lycopenementioning
confidence: 98%
See 1 more Smart Citation
“…Heptane has been used for extraction of carotenoids from tomatoes in a study looking at in vitro approximation of absorption of carotenoids in vivo [9]. Heptane is not nearly as volatile as hexane, so it is much easier to work with, yet the molecular chain length is still very good for extracting the highly nonpolar carotenoids.…”
Section: Methodsmentioning
confidence: 99%
“…One such class of nutrients is carotenoids, acquired mainly from fruit and vegetable intake. Carotenoid bioavailability varies across different foods and different forms of the same food [3,4,5,6]. Based on the correlation corrected for within-person variation, assessment validity with respect to diet records is good for some carotenoid-containing foods (e.g., orange/grapefruit juice ( r = 0.84), eggs ( r = 0.77)), but lower for others (carrots ( r = 0.40), yellow squash ( r = 0.49)) [7].…”
Section: Introductionmentioning
confidence: 99%